Liberalism, Multiculturalism, and the Welfare State - Nicole Selamé G.; Luis Villavicencio M. (Ideas y Valores, 2011)
This article examines whether the politics of difference is consistent with the politics of redistribution that characterizes the welfare state. The paper also explains why Brian Barry’s version of multiculturalism is a caricature, and inquires whether the dichotomy between liberalism and multiculturalism allows for any conciliation. Finally, it revises the pertinence and relevance of the thesis that upholds the compatibility between multiculturalism and the welfare state.